2009
DOI: 10.1002/zoo.20252
|View full text |Cite
|
Sign up to set email alerts
|

Learning from nature: bottlenose dolphin care and husbandry

Abstract: The world's longest-running study of a wild dolphin population, operated by the Chicago Zoological Society since 1989, has focused on the multi-generational resident community of about 160 bottlenose dolphins in Sarasota Bay, Florida, since 1970. Observational and capture-release research on the biology, behavior, life history, ecology, and health of individually identifiable bay residents of up to 59 years of age and spanning five generations has helped to inform collection managers at the Brookfield Zoo and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 75 publications
2
110
0
Order By: Relevance
“…1). The Sarasota Bay dolphin community, which has been monitored and studied since 1970, is a demographically closed population comprised of approximately 160 individuals, the majority of which have known ages, sex, and familial lineages (Wells 2009). Routine photo-ID surveys began in Sarasota in 1980 (Wells 1991(Wells , 2003, and capture-release projects have been conducted since 1970 therefore providing a long-term record of life history parameters, body condition, and health indicators for dolphins in this population (Wells et al 2004).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). The Sarasota Bay dolphin community, which has been monitored and studied since 1970, is a demographically closed population comprised of approximately 160 individuals, the majority of which have known ages, sex, and familial lineages (Wells 2009). Routine photo-ID surveys began in Sarasota in 1980 (Wells 1991(Wells , 2003, and capture-release projects have been conducted since 1970 therefore providing a long-term record of life history parameters, body condition, and health indicators for dolphins in this population (Wells et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…1). Anthropogenic contaminants have been suspected to be associated with lacaziosis occurrence (Van Bressem et al 2007, 2009, 2009; however, chemical contamination may not be explaining the observed differences in LD/LLD bottlenose dolphins on the east and west coasts of Florida as contaminant studies found no significant differences in polychlorinated biphenyls (PCBs), polyfluoralkyls (PFAs) (Houde et al 2005(Houde et al , 2006 or mercury (Bryan et al 2007, Stavros et al 2007) between the 2 populations.…”
Section: Prevalence Comparisonsmentioning
confidence: 99%
See 3 more Smart Citations